Spatial-Coded Phosphor Coating for High-Efficiency White LEDs - Ching-Cherng Sun; Yu-Yu Chang; Chun-Yan Lu; Hsin-Ying Lin; Zi-Yan Ting; Tsung-Hsun Yang; Te-Yuan Chung; Yei-Wei Yu (IEEE Photonics Journal, 2017)
In this paper, a new structure of spatial-coded coating phosphor is proposed and effectively benefits the efficiency enhancement in the white light-emitting diodes (LEDs). The spatial-coded phosphor plate contains two subregions. One subregion is of the yellow phosphor for providing the greatest extracted yellow light, and the other subregion is the open windows for preventing the blue light from the absorption by the yellow phosphor and the Stoke loss in the wavelength conversion. In the design process, the thickness and the concentration of the phosphor and photon recycling in a high-reflectivity cavity are all simulated and optimized. Finally, the predicting spectra of the resultant white LEDs with the spatial-coded phosphors by the simulation model are all in very good agreement with the corresponding spectra from the practical measurements. Moreover, as the correlated color temperature (CCT) is around 6500 K, the maximal packaging efficiency of the white LEDs with the spatial-coded phosphors is as high as 68.0% in the measurement, and the corresponding simulation is 71.8%. It is much higher even than the optimal packaging efficiency of the conventional conformal or remote-dome phosphor packaging structure.